A new species of genus Bonnaya (Linderniaceae) from the Western Ghats of India - Vinod, Shimpale; Vinayak, Sardesai; Sanjay, Sathe (Phytotaxa, 2019)
Bonnaya milindii (Linderniaceae), a new species from the Western Ghats of India is described and illustrated. The species is similar to Bonnaya sanpabloensis but differs in its petaloid staminodes and glabrous corolla.